(untitled) (International Journal of Engineering and Computer Science, 2021)
It is a modern type of technology that empowers virtual and physical artefacts to interact and provide digitized services for each other, and includes the Internet of Things (IoT). But it has some benefits, but raises problems of single point of failure, anonymity, accountability, and data integrity due to the new structured design. Challenges like these stands in the path of the introduction of all the most interesting Internet of Things technologies. Bringing the Internet of Things through the public ledger might fix these issues. Decentralized ledger systems are comprised of blockchain as well as distributed ledgers. The introduction of the Internet of Things (IoT) to the blockchain will offer tremendous advantages. Blockchain integration in this paper offers a detailed exploration of how to combine the IoT technology with the IoT scheme. It is followed by reviewing the basic framework and addressing the problems inherent in the system’s integration, explaining the advantages of it, and describing ways in which the blockchain can help to overcome such problems. Blockchain as a Service for IoT can illustrate how different protocol concepts can be applied using different service types on blockchain. After this, there would be an important section about the integration of artificial intelligence (AI) into the Internet of Things (IoT) and blockchain. Finally, potential study avenues will focus on ways of applying the Internet of Things (IoT) with blockchain are suggested. The open issues and challenges of 5G-enabled IoT for blockchain-based Industrial automation are also analyzed in the text.